Conservative surgical management of immediate post-caesarean uterine dehiscence and pelvis abscess due to proteus mirabilis infection: a rare complication of puerperal endomyometritis - Thyagaraju, Chitra; S., Madhuri Makam; Yedla, Deepthi; Papa, Dasari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Cesarean delivery is the most commonly performed major abdominal operation in women with prevalence ranging from 12% in public sectors to 28% in private sectors in India (DLHS-3 survey). Parallel to this, the complications of surgery are increased. Among these complications, uterine dehiscence and pelvic hematoma with abscess collection is rare but serious complication which might end in hysterectomy. We hereby describe the conservative surgical management of a case of infected uterine incisional necrosis and dehiscence after primary cesarean delivery. We encountered a 25-years-old woman presenting to our emergency department (ED) with severe suprapubic pain and high-grade fever. She had an emergency cesarean delivery performed 14 days prior to presentation due to non-reassuring fetal heart rate. At the ED, ultrasonography revealed collection with septation around uterus with communication into uterine cavity. CT scan of pelvis was ordered and showed an intraperitoneal collection anterior to the uterus at the level of the uterine cesarean scar. Exploratory laparotomy showed a uterine rupture at the previous incision site. We performed resection of necrotic edges, peritoneal lavage, approximation of uterine edges with separate interrupted sutures, placement of a suction drain in the cul-de-sac. During postoperative follow up, patient was stable with no symptoms or signs of uterine/pelvic infection. Conservative management by drainage and resection of necrotic edges in addition to intravenous antibiotics may be considered as an option before resorting to hysterectomy in selected young patients.